2019
DOI: 10.1080/19331681.2019.1651685
|View full text |Cite
|
Sign up to set email alerts
|

Appealing to the base or to the moveable middle? Incumbents’ partisan messaging before the 2016 U.S. congressional elections

Abstract: This paper examines partisan communications of incumbent members of Congress during the nine weeks leading up to the U.S. 2016 election. The central premise is rooted in the median voter theorem, which is coupled with theories of political activation and reinforcement, to show how politicians communicate in order to attract support from large swaths of the public. We analyze the partisanship of tweets posted by incumbents in Congress using mixed-effects models to examine the relationships between party, time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…A comprehensive analysis of Facebook political advertisements from 2018 found that candidates often explicitly portrayed themselves as partisans in ads targeted at their base (Fowler et al 2021). Twitter messages by members of Congress also exhibit open partisanship, but their contents appear markedly more partisan for Republicans, with Democrats still moderating their messages to reach a broader middle (Hemphill and Shapiro 2019;Russell 2021)-an asymmetry that parallels a substantial body of scholarship showing that Republicans are more polarized than Democrats (Pierson and Schickler 2020). And importantly, politicians' partisan Facebook ads and Twitter messages largely focus on party loyalty and contain relatively little discussion of issue positions (Bode et al 2016;Fowler et al 2021;Jungherr 2016).…”
Section: Effects Of Political Polarizationmentioning
confidence: 99%
“…A comprehensive analysis of Facebook political advertisements from 2018 found that candidates often explicitly portrayed themselves as partisans in ads targeted at their base (Fowler et al 2021). Twitter messages by members of Congress also exhibit open partisanship, but their contents appear markedly more partisan for Republicans, with Democrats still moderating their messages to reach a broader middle (Hemphill and Shapiro 2019;Russell 2021)-an asymmetry that parallels a substantial body of scholarship showing that Republicans are more polarized than Democrats (Pierson and Schickler 2020). And importantly, politicians' partisan Facebook ads and Twitter messages largely focus on party loyalty and contain relatively little discussion of issue positions (Bode et al 2016;Fowler et al 2021;Jungherr 2016).…”
Section: Effects Of Political Polarizationmentioning
confidence: 99%
“…Gerodimos and Jusinussen (2015) content analyzed Barack Obama's 2012 presidential campaign Facebook page and found that posts emphasize Obama's image over his policy positions. Hemphill and Shapiro (2019) found that in the 2016 congressional general election, Democrats decreased their partisanship in the weeks leading up to the vote. By contrast Republicans produced equally high volumes of partisan messaging.…”
Section: Types Of Political Campaign Messagingmentioning
confidence: 99%
“…Given the value-balanced orientations of those in host populations with moderate attitudes to immigration-the so-called "moveable middle" that are the explicit target of many recent immigration messaging campaigns (e.g., ICPA (International Centre for Policy Advocacy), 2017; Carter, 2018) based on segmentation analysis of attitudes, "anxieties" and sociodemographic determinants (e.g., More in Common, 2017)-persuasive migration messaging is theoretically most effective when taking a values-balanced approach. This notion of the "moveable middle" has been linked to Downs' 1957 Median Voter Theorem (Hemphill andShapiro, 2019). As such, it should also attempt to mobilize values of its opposition; that is pro-migration messaging should mobilize Schwarz's values of conformity, tradition, security, and power, whereas anti-migration messaging should mobilize values of universalism, benevolence, self-direction, and stimulation.…”
Section: Introductionmentioning
confidence: 99%